MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PEMAHAMAN MATERI ISI KANDUNGAN HADIS SILATURRAHIM DI MI DARUL MUTTAQIN SIDOARJO - Hakiqi, Miftakhul Ilmi (Journal Of Islamic Elementary School (JIES), 2019)
The learning of the Koran Hadith in Darul Muttaqin Sadang’s Madrasah Ibtidaiyah (MI) has not yet reached the specified Minimum Affirmation Criteria, because there is no active involvement of students in learning. Then a strategy can be implemented that can improve the learning outcomes of Al-Quran Hadith material in class IV (four). This study aims (1). Knowing the effectiveness of applying the cooperative learning type Think Pair Share (2). Knowing the increase in students’ understanding by using the cooperative learning type Think Pair Share material content content Hadith in the learning of Al-Quran Hadith in MI Darul Muttaqin. This type of research is classroom action research conducted in two cycles, the research model conducted is the Kurt Lewin model, where in two cycles consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques obtained from observation, tests, interviews, and documentation. The results of the study show that (1). The application of the Think Pair Share type cooperative learning model runs effectively through improvements in each cycle. In the process of teaching and learning it is known that the activities of teachers and students have increased from pre-cycle, cycle I, and cycle II to the final score of 84.6 (good). (2). The score of students’ pre-cycle comprehension of 55.9 (less) increased to 57.4 (sufficient) in cycle I. Classically it was not completed and did not meet the KKM, then increased in the second cycle to 82.4 (very good). Likewise with student mastery learning from the pre-cycle get a score of 8.2% (less) and increase to 13.5% (less) in the first cycle and for silus II to 97.3% (very good) according to the results of the study at MI Darul Muttaqin Sadang.